Management of Patients when Superficial Venous Disease Arises from Pelvic Escape Points - Ahuja, Rakesh S.; Garg, Tushar; Sudheendra, Deepak (Seminars in Interventional Radiology, 2021)
Chronic pelvic pain (CPP) is a common condition in women that carries with it significant morbidity. It is commonly seen in patients presenting to obstetrics and gynecology outpatient clinic visits. CPP is a presenting symptom of various pathologies including pelvic varicocele, pelvic adhesions, spastic colon syndrome, uterine fibroids, endometriosis, and psychosomatic disorders. Pelvic congestion syndrome has more recently been termed “pelvic venous insufficiency (PVI)” due to the underlying retrograde flow through incompetent ovarian and pelvic veins that are thought to cause the symptoms of CPP. Pelvic varices can commonly present alongside vulvar, perineal, and lower extremity varices. There are some predictable “escape pathways” for these varices that may present for interventional treatment. This article introduces the reader to current terminology, clinical presentation, diagnosis, and treatment of patients with pelvic varices due to PVI.
Keywords: pelvic varices; pelvic congestion syndrome; pelvic venous insufficiency; embolization; sclerotherapy; interventional radiology